Idarubicin, cytarabine, and pravastatin as induction therapy for untreated acute myeloid leukemia and high‐risk myelodysplastic syndrome. Issue 6 (27th February 2015) - Shadman, Mazyar; Mawad, Raya; Dean, Carol; Chen, Tara L.; Shannon‐Dorcy, Kathleen; Sandhu, Vicky; Hendrie, Paul C.; Scott, Bart L.; Walter, Rol B.; Becker, Pamela S.; Pagel, John M.; Estey, Elihu H.
<x xml:space="preserve">Abstract</x> Previous studies suggest that idarubicin/cytarabine(ara‐C)/pravastatin (IAP) is an active salvage regimen for patients with AML. We therefore investigated this regimen in patients with newly‐diagnosed AML or MDS (≥10% blasts). Patients were eligible if the anticipated treatment‐related mortality (TRM) was <10%. Patients received pravastatin (1, 280 mg/day po; days 1–8), cytarabine (1.5 g/m2/day; days 4–7), and idarubicin (12 mg/m2/day, days 4–6). Up to 3 cycles of consolidation with a shortened course was permitted. The primary endpoints were "good CR" rate (CR on day 35 without minimal residual disease) and TRM in the first 28 days. The study was to stop if after each cohort of 5 patients (a) the Bayesian posterior probability was < 5% that the true "good CR rate" was ≥ 70% or (b) the posterior probability was >25% that the TRM rate was ≥5%. Twenty‐four patients were included. Conventional CR was achieved in 15 (63%) patients but only 12 (50%) achieved "good CR". 4 of 12 (33%) patients with "good CR" relapsed at median of 16 weeks (10.5–19). Five (21%) patients had refractory disease. Survival probability at 1 year was 72% (48.7–64). Two (8.3%) patients died within 28 days from multiorgan failure. The most common grade 3–4 adverse effects were febrile neutropenia (75%) and diarrhea (25%). Based on the stopping rules accrual ceased after entry of these 24 patients. IAP did not meet the predefined efficacy criteria for success. Therefore, we would not recommend this regimen for phase three testing in this patient subset. Am. J. Hematol. 90:483–486, 2015. © 2015 Wiley Periodicals, Inc.